Amoral Communities : Collective Crimes in Time of War - Dragojević, Mila (Book collections on Project MUSE., 2019)
"This book shows how amoral communities - places where wartime violence against civilians is both tolerated and justified by the respective authorities - are created when the complementary processes of the exclusion of moderates and the production of borders connect ethnicity or other cultural identity with political orientation on the local level"--